Practical high-performance liquid chromatography. - Meyer, Veronika R., 1951- (Chichester : Wiley, 2010)
Jump into the HPLC adventure! Three decades on from publication of the 1st German edition of Veronika Meyer's book on HPLC, this classic text remains one of the few titles available on general HPLC aimed at practitioners. New sections on the following topics have been included in this fifth edition: Comparison of HPLC with capillary electrophoresis How to obtain peak capacity van Deemter curves and other coherences Hydrophilic interaction chromatography Method transfer Comprehensive two-dimensional HPLC Fast separations at 1000 bar HPLC with superheated water In addition, two chapters on the instrument test and troubleshooting in the appendix have been updated and expanded by Bruno E. Lendi, and many details have been improved and numerous references added. A completely new chapter is presented on quality assurance covering: Is it worth the effort? Verification with a second method Method validation Standard operating procedures Measurement uncertainty Qualifications, instrument test, and system suitability test The quest for quality